Utilization of The Chronic Disease Management Program During The Covid-19 Pandemic - Azizah, Andi Nur; Raodhah, Sitti; Surahmawati, Surahmawati; Alam, Syamsul (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
The increasing number of chronic diseases such as hypertension and diabetes mellitus has made the government through Health BPJS promote and prevent through chronic disease management programs (Prolanis). The occurrence of the Covid-19 pandemic has changed all aspects of life including Prolanis activities. This study aims to determine the use of the chronic disease management program (Prolanis) during the Covid-19 pandemic at the Tamamaung public health center, Makassar City with this type of qualitative research. Determination of informants in this study using a purposive sampling technique. The informants in this study consisted of Prolanis management officers, Prolanis participants who suffered from hypertension, and type 2 diabetes mellitus. Data was collected through in-depth interviews with informants. The results of the study explained that the use of Prolanis during the Covid-19 pandemic still received support from families by reminding each other to maintain health. Health workers continue to serve participants as usual for medical examinations and routine monthly administration of drugs unless education and gymnastics are temporarily prevented The need for health services, where participants feel they still need exercise and education activities. However, due to the Covid-19 pandemic, participants can only carry out health checks and take routine medicine every month. It is recommended that health workers continue to increase their role as educators by providing education to Prolanis participants both during the Covid-19 pandemic period and after the pandemic ends and emphasizing the importance of joining Prolanis.